2016
DOI: 10.1103/physrevb.94.155445
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of nonlocal Cooper-pair transport and of a singlet-triplet transition in the critical current of a double-quantum-dot Josephson junction

Abstract: We study the critical Josephson current flowing through a double quantum dot weakly coupled to two superconducting leads. We use analytical as well as numerical methods to investigate this setup in the limit of small and large bandwidth leads in all possible charging states, where we account for on-site interactions exactly. Our results provide clear signatures of nonlocal spin-entangled pairs, which support interpretations of recent experiments [Deacon, R. S. et al., Nat. Commun. 6, 7446 (2015)]. In addition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…[42] and [43] for recent reviews on experiments and theory, respectively. In particular, there are investigations of the Josephson effect through quantum dots [44][45][46][47][48][49], multiple Andreev reflections [50][51][52][53][54][55], the interplay between superconducting correlations and the Kondo effect [56][57][58][59][60][61], the generation of unconventional superconducting correlations in quantum dots [62][63][64][65], Cooper pair splitting [66][67][68][69][70][71] and the generation of Majorana fermions [72][73][74][75]. Thermoelectric effects in superconductor-quantum dot hybrids have been studied in the absence of Coulomb interactions [76].…”
Section: Introductionmentioning
confidence: 99%
“…[42] and [43] for recent reviews on experiments and theory, respectively. In particular, there are investigations of the Josephson effect through quantum dots [44][45][46][47][48][49], multiple Andreev reflections [50][51][52][53][54][55], the interplay between superconducting correlations and the Kondo effect [56][57][58][59][60][61], the generation of unconventional superconducting correlations in quantum dots [62][63][64][65], Cooper pair splitting [66][67][68][69][70][71] and the generation of Majorana fermions [72][73][74][75]. Thermoelectric effects in superconductor-quantum dot hybrids have been studied in the absence of Coulomb interactions [76].…”
Section: Introductionmentioning
confidence: 99%
“…These ground states can be obtained by tuning the DQD energy, ε δ > 0 corresponding to empty quantum dot, and ε δ < 0 corresponding to the single electron occupation. In the case where the quantum dots are singly occupied we consider only singlet state since it is the ground state of DQD in the strong Coulomb interaction limit 44 . It can also be shown that the nonlocal contribution to the Josephson current is absent for |T 0 , |↑↑ , |↓↓ DQD ground states when U → ∞ 49 .…”
Section: Josephson Currentmentioning
confidence: 99%
“…In addition, we assume that k B T ≪ J, therefore we can neglect the thermal excitation of the triplet states. Here J denotes the exchange interaction between the quantum dots (via superconducting electrodes) that can be also calculated with the 4-th order perturbation theory 44,49 . Since we consider the superconducting electrodes with the superconducting gap ∆ in the quasiparticle density of states with assumption ∆ ≫ k B T K one can neglect the effect of Kondo correlations on the value of the exchange interaction J.…”
Section: Josephson Currentmentioning
confidence: 99%
“…Several previous works on similar systems completely neglect the possibility of EC processes [7,5254 7172]. In other works EC coupling is taken into account [44,61,6465 6768 73], but in most of the cases it is defined as a constant coupling term that is equivalent to the IT coupling used here, therefore they can be incorporated to the same term. However, as we demonstrate below, in certain models the EC term is not constant, but it can depend on the on-site energies of the QDs.…”
Section: Introductionmentioning
confidence: 99%